İcra hukukunda menfi tespit davası - Konyar, Hanife (My University, 2001)
Şekli hukuk kurallarıyla devam eden icra takibi içerisinde, kendisine gönderilen ödeme emrine süresinde itiraz etmeyen veya itiraz edipte, bu itirazı, dar bir delil sistemi içerisinde inceleme yetkisi bulunan tetkik mercii tarafından kaldırılan kişi, gerçekte borçlu olmasa dahi takip hukuku bakımından borçlu sayılmaktadır. Maddi hukuk ile takip hukuku arasında oluşabilecek farklılıkları ortadan kaldırmak amacıyla düzenlenmiş olan menfi tespit davasını borçlu, borcunu cebri icra tehdidi altında ve fakat henüz icra dairesine ödememiş iken açabilecektir. Tezin konusunu oluşturan menfi tespit davası İcra İflas Kanunumuzun 72. maddesinde düzenlenmiştir. Bu davanın, cebri icra içerisindeki yeri ve cebri icraya olan etkileri ayrıntılı olarak incelenmiştir. Menfi tespit davası düzenlenirken, alacaklının ve borçlunun menfaatlerinin dengelenmesi önemli bir husustur. Kanunumuzda menfi tespit davasına ilişkin düzenleme genel itibariyle yerindedir. Ancak, yapılan kanun değişikliği ile teminat miktarının, asgari tazminat miktarının altında kalması, dava alacaklı lehine sonuçlandığında, onun aleyhine bir husus olmaktadır. Tezde, İİK. m. 72’de düzenlenen menfi tespit davası içerisinde oluşabilecek sorunlar, doktrindeki tartışmalar ve Yargıtay’ın görüşleri aktarılarak çözümlenmiştir.

The person who did not take an exception within the period of payment order which notified to him/ her or in case of following his/ her objection the said exception has been abolished by the competent enforcement court within the frame of limited evidence within the executive proceeding which has been continuing with adjective law, and the said person has deemed as a debtor according to the prosecution law even the said person has not a debtor. A debtor can file the negative declaratory action which has been prepared in order to eliminate the differences which could be occurred between the actual law and prosecution law under the enforcement of a court decision threat and while the said debt has not been paid to the enforcement office yet by the said debtor. The negative declaratory action which consist the subject of the thesis has indicated in the article 72nd of the Execution and Bankrupt Law. It has been studied the status of the said action in the enforcement of a court decision and its effects to the enforcement of a court decision in details. The fact of balancing the beneficial interests of creditor and debt is an important matter. The regulations have appropriated in our law regarding the negative declaratory action in general. However, remaining the security amount under the minimum-security amount is a negative matter when the action has resulted in favor of the creditor as a result of the modified of the related law. The problems which could be occurred within the frame of negative declaration action which has been prepared in the article 72nd of the Execution and Bankrupt Law has solved with adaptation of the Supreme Court of Appeals in the present thesis.
Keywords: Hukuk-icra Hukuku